Generation lengths of the world's birds and their implications for extinction risk. Issue 5 (6th May 2020) - Bird, Jeremy P.; Martin, Robert; Akçakaya, H. Reşit; Gilroy, James; Burfield, Ian J.; Garnett, Stephen T.; Symes, Andy; Taylor, Joseph; Şekercioğlu, Çağan H.; Butchart, Stuart H. M.
Abstract: Birds have been comprehensively assessed on the International Union for Conservation of Nature (IUCN) Red List more times than any other taxonomic group. However, to date, generation lengths have not been systematically estimated to scale population trends when undertaking assessments, as required by the criteria of the IUCN Red List. We compiled information from major databases of published life‐history and trait data for all birds and imputed missing life‐history data as a function of species traits with generalized linear mixed models. Generation lengths were derived for all species, based on our modeled values of age at first breeding, maximum longevity, and annual adult survival. The resulting generation lengths varied from 1.42 to 27.87 years (median 2.99). Most species (61%) had generation lengths <3.33 years, meaning that the period of 3 generations—over which population declines are assessed under criterion A—was <10 years, which is the value used for IUCN Red List assessments of species with short generation times. For these species, our trait‐informed estimates of generation length suggested that 10 years is a robust precautionary value for threat assessment. In other cases, however, for whole families, genera, or individual species, generation length had a substantial impact on their estimated extinction risk, resulting in higher extinction risk in long‐lived species than in short‐lived species. Although our approach effectively addressed data gaps, generation lengths for some species may have been underestimated due to a paucity of life‐history data. Overall, our results will strengthen future extinction‐risk assessments and augment key databases of avian life‐history and trait data. Abstract : Article impact statement : Accurate generation lengths for all birds will improve the assessment of extinction risk within the group. Abstract : Duraciones Generacionales de las Aves del Mundo y sus Implicaciones para el Riesgo de Extinción Resumen: Las aves han sido valoradas integralmente en la Lista Roja de la Unión Internacional para la Conservación de la Naturaleza (UICN) más veces que cualquier otro grupo taxonómico. Sin embargo, a la fecha, las duraciones generacionales no han sido estimadas sistemáticamente para escalar las tendencias poblacionales cuando se realizan las valoraciones, como lo requieren los criterios de la Lista Roja de la UICN. Compilamos información a partir de las principales bases de datos de historias de vida y datos de características publicadas para todas las aves e imputamos los datos faltantes de historias de vida como una función de las características de especies con modelos lineales mixtos generalizados. La duración por generación estuvo derivada para todas las especies con base en nuestros valores modelados de edad durante la primera reproducción, la longevidad máxima y la supervivencia anual de adultos. La duración por generación resultante varió de 1.42 a 27.87 años (mediana: 2.99). La mayoría de las especies (61%) tuvo una duración generacional <3.33 años, lo que significa que el periodo de tres generaciones ‐ durante el cual se valoran las declinaciones poblacionales bajo el Criterio A ‐ es <10 años, el cual es el valor usado por la Lista Roja de la UICN para la valoración de especies con tiempos generacionales cortos. Para estas especies, nuestras estimaciones de duración por generación informados por características sugieren que diez años es un valor preventivo sólido para la valoración de amenazas. Para otros casos, sin embargo, como familias o géneros enteros o especies individuales, la duración generacional tuvo un impacto sustancial sobre su riesgo de extinción estimado, resultando así en un riesgo de extinción más elevado para las especies con mayor longevidad que aquellas especies con una menor longevidad. Aunque nuestra estrategia lidió efectivamente con los vacíos en los datos, la duración generacional para algunas especies podría estar subestimada debido a la escasez de datos de historia de vida. En general, nuestros resultados fortalecerán las futuras valoraciones de extinción de riesgo y aumentarán las bases de datos importantes de la historia de vida de las aves y los datos de características. 摘要: 在《世界自然保护联盟 (IUCN) 濒危物种红色名录》中, 鸟类被全面评估的次数比其它任何类群都要多。然而, 目前的评估尚未按照《IUCN红色名单》标准的要求, 系统地估计世代时间来计算种群趋势。我们从已发表的所有鸟类生活史及特征数据的几大数据库中整理了信息, 并用广义线性混合模型构建物种特征的函数对缺失的生活史数据进行了估计。我们进而基于对初次繁殖年龄、最长寿命和成体年均存活率的模拟值, 获得了所有物种的世代时间。得到的鸟类世代时间从 1.42 年到 27.87 年不等 (中位数为 2.99 年) 。大多数物种 (61%) 的世代时间小于 3.33 年, 意味着三个时代的时长小于 10 年, 而这是《 IUCN 红色名录》评估标准 A 中对种群下降的评估周期, 用于评估世代时间短的物种。对于这些物种, 基于特征估计的世代时间表明, 10 年是评估威胁的一个稳健预警值。而在其他情况下, 世代时间对于估计整个科、属或个别物种的灭绝风险有重大影响, 结果导致寿命长的物种灭绝风险高于寿命短的物种。虽然我们的方法有效地解决了数据缺失的问题, 但由于一些物种生活史数据缺乏, 其世代时间可能会被低估。总的来说, 我们的研究结果将强化未来的灭绝风险评估, 并扩增鸟类生活史和特征数据的关键数据库。 【翻译: 胡怡思; 审校: 聂永刚】